Inflammation Regulates TMPRSS6 Expression via STAT5 - Meynard, Delphine (Public Library of Science, 2013)
TMPRSS6 is a regulated gene, with a crucial role in the regulation of iron homeostasis by inhibiting hepcidin expression. The main regulator of iron homeostasis, the antimicrobial peptide hepcidin, which also has a role in immunity, is directly upregulated by inflammation. In this study, we analyzed whether inflammation is also a modulator of TMPRSS6 expression in vitro and in vivo and we determined the mechanism of this regulation A Human Hepatoma cell line was treated with interleukin-6 and mice were injected with lipopolysaccharide and TMPRSS6 expression and the regulatory mechanism were addressed. In this study, we demonstrate that inflammation downregulates TMPRSS6 expression in vitro and in vivo. The downregulation of Tmprss6 by inflammation in mice is not dependent on the Bmp-Smad pathway but occurs through a decrease in Stat5 phosphorylation. Moreover, Stat5 positively regulates Tmprss6 expression directly by binding to a Stat5 element located on the Tmprss6 promoter. Importantly, our results highlight the functional role of inflammatory modulation of TMPRSS6 expression in the regulation of hepcidin. TMPRSS6 inhibition via decreased STAT5 phosphorylation may be an additional mechanism by which inflammation stimulates hepcidin expression to regulate iron homeostasis and immunity.